Screw dislocation in a Bi-medium within strain gradient elasticity revisited - Davoudi Kamyar M.; Aifantis Elias C. (Journal of the Mechanical Behavior of Materials, 2019)
In this paper, we consider a straight screw dis-location near a flat interface between two elastic media in the framework of strain gradient elasticity (as studied by Gutkin et. al. [1]) by now taking care of some incomplete calculations). Closed form solutions for stress components and the Peach-Koehler force on the dislocation have been derived. It is shown that the singularities of the stress components at the dislocation line are eliminated and both components are continuous and smooth across the interface. The effect of the distance of the dislocation position from the interface on the maximum value of stress is investigated. Unlike in the case of classical solution, the image force remains finite when the dislocation approaches the interface. It is shown that the dislocation is attracted by the medium with smaller shear modulus or smaller gradient coefficient.